Kinematic differences between successful and faulty spikes in young volleyball players - Sarvestan, J.; Svoboda, Z.; Linduška, P. (Journal of Sports Sciences, 2020)
This study was designated to investigate the kinematical differences between successful and faulty spikes, in order to identify the best strategies leading to better spike performance. Simulating a real-game condition, 13 elite youth attackers performed 6 spikes in the presence of 2 blocks. The kinematic variables of the spike performances were recorded using 6 optoelectronic cameras (Vicon Motion systems, Oxford, UK). The paired sample t-test was used to compare the kinematic variables recorded during the delivery of successful and faulty spikes. Among the successful trials, both the angular velocities of the knees (˜12.4%) and hips (˜13.3%), and the vertical velocity of the centre of mass at take-off (˜6.5%) and arm swing (˜8.2%) were considerably higher during the plant phase. Consequently, the jump (˜4.3%) and spike (˜1.5%) heights, as well as the wrist velocity (˜5.5%), were significantly higher during the jump phase of successful spikes. In successful spike performances, the attackers adopted higher hip and knee angular velocities, combined with efficient arm swings, to produce higher take-off velocities and reach higher jump heights. This approach provides them with the better position regarding the ball and the blockers to find the best path and hit the ball with higher arm velocities.Kinematische Unterschiede zwischen erfolgreichen und fehlerhaften Schmetterschlägen bei jungen Volleyballspielern